Meningkatkan Kemampuan Membaca Permulaan Melalui Media Stick Abjad pada Anak Usia Dini - Nasution, Adelia Hanjani; NurHayani, NurHayani (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2024)
This research article has the objectives of 1) to find out children's reading skills at the beginning 2) to find out children's reading abilities through stick media 3) and to find out the obstacles and solutions made by teachers in teaching children's reading beginners. This study is located at TK Raudataul Ilmi Medan. To obtain data, researchers used descriptive qualitative research methods. Data collection techniques through interviews, observation and documentation. Then, to maintain the validity of the data, researchers used triangulation. The results were found. 1) The ability of children at Kindergarten Raudatul Ilmi Medan in the new academic year, the results of the survey revealed that the ability of children could not read, but only knew the alphabet. 2) The ability to read children at the beginning through the media of alphabet sticks, gives significance for children to know the alphabet and read at the beginning. 3) Obstacles and solutions are felt by the teacher as children are more fun playing than learning presented by the teacher, even though they are already using stick media. This is then, the teacher takes action on the analysis of media that is varied and collaborates with the children's parents to accelerate children's reading skills. Keywords: Beginning Reading, Media Stick, Early Childhood.